Profil Nilai C-Reactive Protein (CRP) pada Pasien Tuberkulosis Paru dan Tuberkulosis Ekstra Paru di RSUD Waled - Nova Nova; Isti Noviani; Dwi Rosa Eka Agustina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Tuberculosis is a chronic infectious disease caused by the bacterium Mycobacterium tuberculosis. Based on the infected organ, tuberculosis is divided into extra-pulmonary tuberculosis and pulmonary tuberculosis (TB). C-Reactive Protein (CRP) is a protein found in the blood that increases in response to inflammation. CRP can be used as a marker of tuberculosis activity and severity and can predict the course of the disease. To determine profile of c-reactive protein (crp) values in tb & ekstrapulmonary tb patients at rsud waled. This observational study used a cross sectional design. Samples were taken from medical records using a Total Sampling within 100 patients. The research conducted at Waled hospital in June 2024. The resulted showed that the majority of CRP levels increased in 44 pulmonary TB patients (48.9%) and 8 extrapulmonary TB patients (80%). CRP levels increased in 24 adult pulmonary TB patients (26.7%), 20 elderly pulmonary TB patients (22.2%), while in adult and elderly extrapulmonary TB patients there were 4 people each (40%). CRP levels increased in 27 male pulmonary TB patients (30%), 17 female pulmonary TB patients (19%), while in 5 male extrapulmonary TB patients (50%) and 3 female patients (30%). C-Reactive protein level of pulmonary TB higher than extra pulmonary TB.